Use Of Comic-Based Learning Media In Economics Subject - Rusmaini Rusmaini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Learning media related to the world of education is a tool, an intermediary in delivering material related to messages or lesson information. Thus the learning media certainly has a purpose. The purpose of learning media is to increase new interest, understanding, motivation and stimulation in the learning process. One of the interesting and interactive learning media, especially in economics subjects, is comic-based learning media. This study uses a qualitative approach, namely to describe and describe the influence of the use of instructional media in the world of education. So the results obtained are that comics can make the teaching and learning process effective, increase student interest in learning, and generate interest in student appreciation. Thus the existence of comics as a learning medium can certainly help increase the potential of students, especially in economics subjects. Students can feel the emotion in the pictures presented and the comic language is light because there are not many sentences to read which tends to make the reader lazy to read. So with the existence of comics as a learning medium can increase interest in learning better and cultivate reading.